Associations of CRP and PCT levels with obstetric and neonatal outcomes: a prospective study - Merve Ates; Pinar Calis; A. Gokcen Artiktay; Canan Yilmaz; Ibrahim Murat Hirfanoglu; Ahmet Erdem; Mehmet Erdem (BMC Pregnancy and Childbirth)
Abstract Background C-reactive protein (CRP) and procalcitonin (PCT) levels may be elevated under inflammatory conditions. The aim of this study was to determine the cutoff values for CRP and PCT levels during pregnancy and to evaluate the associations of any elevation with obstetric and neonatal outcomes. Methods This prospective study was conducted from June 2023 to December 2024. The study included 411 singleton pregnant women aged 18–44 years with no apparent clinical infection. Venous blood samples were collected during the visit for routine antenatal care during all three trimesters. Categorical variables were compared between groups via the chi-square test, and Student’s t-test was used to compare normally distributed continuous variables. The area under the ROC curve was used to detect sensitivity and specificity and to set a cutoff. Regression analysis was performed to evaluate the effects of age and BMI on obstetric complications. P values < 0.05 were considered statistically significant. Results The mean CRP and PCT levels in the study group were 10.9 ± 16.7 and 0.17 ± 1.8, respectively. ROC curves were used to analyze the ability of CRP and PCT values during pregnancy to predict obstetric complications. A cutoff value of 6.72 mg/L (sensitivity: 67%; specificity: 60%) and 0.0385 (sensitivity: 60%; specificity: 61%) was revealed. The incidence of composite obstetric complications was significantly greater in patients with elevated CRP levels (32.4% vs. 67.6%) (p < 0.001). The incidence of preeclampsia, GHT, neonatal complications and the need for intensive care were significantly greater in patients with CRP levels > 6.72. The incidence of composite obstetric complications was significantly greater in patients with elevated PCT levels (59% vs. 41%) (p < 0.001). Patients with elevated PCT levels had a greater frequency of preterm labor or PPROM, neonatal complications, need for intensive care, and RDS. Conclusions Elevated CRP and PCT are associated with increased rates of obstetric and neonatal complications. CRP and PCT, which are inexpensive and available, may be used for screening to predict obstetric and neonatal complications during patient follow-up. Trial registration This study was approved by the institutional ethical committee of the Gazi University Faculty of Medicine (Approval No:05.06.2023/479).